Congruent changes in microbial community dynamics and ecosystem methane fluxes following natural drought in two restored fens. (September 2021) - Unger, Viktoria; Liebner, Susanne; Koebsch, Franziska; Yang, Sizhong; Horn, Fabian; Sachs, Torsten; Kallmeyer, Jens; Knorr, Klaus-Holger; Rehder, Gregor; Gottschalk, Pia; Jurasinski, Gerald
Abstract : Both the frequency and intensity of drought events are expected to increase, with unresolved alterations to peatland methane cycling and the involved microbial communities. While existing studies have assessed drought effects via experimental approaches under controlled conditions, to our knowledge, no studies have examined the in-situ effects of natural drought in restored temperate fens. In this study, we used quantitative polymerase chain reaction (qPCR) and high throughput 16S rRNA gene amplicon sequencing of DNA and complementary DNA (cDNA) to determine the abundances and community structure of total and putatively active microbial communities following the 2018 European summer drought. Together with geochemical and methane flux data, we compared these results to a non-drought reference dataset. During drought, water level and methane flux rates decreased to a new recent minimum in both fens. This corresponded with pronounced shifts in porewater geochemistry. Microbial community composition in the drought year differed markedly, and was characterized by a greater relative and total abundance of aerobic methanotrophs, and, in one of the two sites, by a decrease in total methanogen abundance. In contrast to the non-drought reference years, type I methanotrophs were clearly more dominant than type II methanotrophs in both fens. cDNA sequencing confirmed the activity of type I methanotrophs during drought, with Methylomonaceae having the highest average relative abundance of bacterial cDNA transcripts. We show that changes in microbial community dynamics, porewater geochemistry, and ecosystem methane fluxes can be substantial following natural drought in restored fens, and provide the first in-situ evidence from a natural drought which suggests type I methanotroph populations are more active than type II methanotrophs in response to drought effects. Type I methanotrophs may represent a key microbial control over methane emissions in restored temperate fens subject to natural drought. Highlights: Drought decreased water level and ecosystem methane fluxes substantially. Microbial community dynamics reflected drought conditions at the sites. Methanogen gene abundances decreased in one of the two fens. Proportion of type II methanotrophs was low and similar to a non-drought year. Type I methanotrophs dominated the active bacterial community profile at both sites.